Evaluation of FLT-PET/CT usefulness in diagnosis and qualification for surgical treatment of gastric cancer - Staniuk, Tomasz; Zegarski, Wojciech; Małkowski, Bogdan; Jankowski, Michał; Klag, Michał; Pietrzak, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Evaluation of FLT/PET/ CT usefulness in diagnosis and qualification for surgical treatment of gastric cancer. Material and methods: The FLT/PET/CT test was carried out in a group of 50 gastric cancer patients. Based on the test result, a decision followed about the therapeutic procedure to be applied. A comparison was made with regards to the consistency of the cancer growth advancement degree evaluation in the initial preoperative FLT/PET/CT test against the evaluation of postoperative degree of cancer advancement in histopathology. Results: In the group of 50 diagnosed patients a surgical treatment was used for 37 patients. 21 resections were performed out of which 19 operations were radical In the group of 16 non-resective operations 2 post-laparotomic patients were selected for inductive treatment. In the group of 13 patients who did not undergo any surgery, 10 were directed to palliative care and 3 for inductive treatment. In the group of 50 patients, the applied FLT-PET/CT test confirmed presence of primary tumor in 49 patients. The presence of increased uptake of FLT in the local lymph nodes during the preoperative FLT-PET/CT test was confirmed in 22 cases. In 14 patients with FLT-PET/Ct N(+) with the M(–) feature resection surgery was performed. The increased uptake of FLT in localizing metastases (nodal and non-nodal) FLT-PET/CT (M+) was detected in 22 patients. The presence of nodal metastases in the postoperative histopathology examination (hpN+) was detected in 14 cases. In these cases preoperative FLT-PET/CT test proved the N(+) feature in 11 patients. The result FLT-PET/CT N(–) was truly negative in 2 patients, and false negative in 1 patient. In the group of 7 operated hpN(–) patients, in 3 patients a preoperative result FLT-PET/ CT N(+) (false positive result) was obtained. The consistency (positive) of nodal metastases identification in FLT-PET/CT as compared to post-surgical histopathology examination scored 11/15, which equals 73.3%. In the group of patients in whom resection surgery was performed, 4 false negative results were obtained [hp(N+), FLT-PET/CT (N–)] and 3 false positive results [hp(N–), FLT-PET/CT N(+)]. Conclusions: The initial test results indicate that FLT-PET/CT is an effective method in evaluating the primary tumor and the regional lymph nodes and is useful and beneficial in the diagnosis and further treatment evaluation of gastric cancer. FLT-PET/CT examination facilitates making proper therapeutic decisions – it allows the number of unnecessary laparotomies to be lowered.